Randomized trial investigating zirconia electroplated telescopic retainers: quality of life outcomes - Schwindling, Franz Sebastian; Deisenhofer, Ulrich; Rammelsberg, Peter; Stober, Thomas (Clinical oral investigations, 2017)
ObjectivesThe study aims to evaluate the effect of electroplated telescopic removable dental prostheses (E-RDPs) with zirconia primary crowns on oral-health-related quality of life (OHRQoL).Materials and methodsFor E-RDPs, electroplating is used to produce precisely fitting gold copings on telescopic primary crowns. These copings are bonded intra-orally to the denture framework. Fifty-six participants in need of 60 removable restorations were randomly allocated one of two materials for the primary crowns: cobalt-chromium alloy or zirconia. OHRQoL was assessed by use of the 49-item Oral Health Impact Profile (OHIP-49) and by additional patient self-rating at baseline before treatment, and after 6 and 12 months. Statistical analysis was performed by use of one- and two-sample t-tests and analysis of covariance.ResultsMean OHIP sum score at baseline was 53.4 (SD 37.4, 95 % CI 41.3-62). At follow-ups, it decreased significantly (after 6 months: mean 20, SD 26, 95 % CI 13-27.1; after 12 months: mean 16.4, SD 17.9, 95 % CI 11.6-21.2). The mean reduction in OHIP sum score after 12 months was 25 (SD 31.2, 95 % CI 13.1-36.9) for cobalt-chromium alloy and 44.4 (SD 32.3, 95 % CI 31.1-57.8) for zirconia. However, no statistically significant difference of the two materials on OHIP change or patient self-rating was detected.ConclusionsAlthough OHRQoL was improved by using both cobalt-chromium alloy and zirconia primary crowns for E-RDPs, post-treatment differences between the groups were not statistically significant.Clinical relevanceZirconia E-RDPs enhance OHRQoL. However, zirconia primary crowns do not outperform cobalt-chromium alloy crowns regarding patient satisfaction—despite their tooth-like color.
Published online: 9 June 2016
Gesehen am 19.06.2018